2022
DOI: 10.33448/rsd-v11i10.31884
|View full text |Cite
|
Sign up to set email alerts
|

Papel do enfermeiro na integridade emocional e física dos pacientes no pós cirúrgico um estudo de revisão de literatura

Abstract: O presente estudo teve como objetivo descrever as principais contribuições que a equipe de enfermagem traz na recuperação física e no controle emocional dos pacientes no momento pós-cirúrgico. Para responder a este objetivo foi adotada como metodologia a Revisão Integrativa de Literatura. Percorrendo seis etapas, identificação do tema, definição do problema, elaboração da pergunta norteadora, a qual foi construída através do acrônimo PICo, busca nas bases de dados, seleção dos estudos que compuseram a amostra,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Other factors contributing to fear of hospitalization include the efects of the disease, being away from family, and a lack of confdence in medical professionals [2,4]. Evidence has also revealed that awareness of self-care behaviors, nurse behavior, level of health literacy, depth of knowledge, kind of illness, education, occupation, sex, and age are all linked to fear of hospitalization [5,6]. Since fear of hospitalization is one of the emotional responses to hospitalization that can be linked to poor patient outcomes, prevention, early diagnosis, and treatment are encouraged [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors contributing to fear of hospitalization include the efects of the disease, being away from family, and a lack of confdence in medical professionals [2,4]. Evidence has also revealed that awareness of self-care behaviors, nurse behavior, level of health literacy, depth of knowledge, kind of illness, education, occupation, sex, and age are all linked to fear of hospitalization [5,6]. Since fear of hospitalization is one of the emotional responses to hospitalization that can be linked to poor patient outcomes, prevention, early diagnosis, and treatment are encouraged [7].…”
Section: Introductionmentioning
confidence: 99%